2021
DOI: 10.3389/fpsyg.2021.648592
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Modalities in Higher Education During the Pandemic: Responses to Coronavirus Disease 2019 From Spain

Abstract: The effects of the pandemic have affected and continue to affect education methods every day. The education methods are not immune to the pandemic periods we are facing, so teachers must know how to adapt their methods in such a way that teaching, and its quality, is not negatively affected. This study provides an overview of different types of teaching methodology before, during, and after the coronavirus disease 2019 (COVID-19) pandemic. This study describes the different types of teaching (e.g., presence le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 39 publications
2
49
0
1
Order By: Relevance
“…The challenges performed by Covid-19 can be interpreted as unique possibilities to test new materials, resources and methods against traditional teaching (Byrnes, Kiely, Dunne, McDermott, & Coffey, 2021). Several authors noted that tutors were trained in new online methodologies, and they showed interest in learning new teaching tools for teaching in the new reality and detected challenges (Verde & Valero, 2021). Tutor performance in the remote study process was influenced by several factors, including the time-consuming creation of materials for online teaching, the availability of technical support during the implementation of them in the estudies and the wide range of strategies to facilitate distance education (Bani Hani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The challenges performed by Covid-19 can be interpreted as unique possibilities to test new materials, resources and methods against traditional teaching (Byrnes, Kiely, Dunne, McDermott, & Coffey, 2021). Several authors noted that tutors were trained in new online methodologies, and they showed interest in learning new teaching tools for teaching in the new reality and detected challenges (Verde & Valero, 2021). Tutor performance in the remote study process was influenced by several factors, including the time-consuming creation of materials for online teaching, the availability of technical support during the implementation of them in the estudies and the wide range of strategies to facilitate distance education (Bani Hani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This opens up a path for the use of new technologies (such as the last one, interactive videos [49]) as a common practice in higher-education studies, including via a hybrid educational model (HyFlex + Tec) and a Massive Open Online Course (MOOC) [50]. Although the application of these new methodologies, mainly MOOCs, has its advantages and disadvantages [51,52], these new teaching methods can significantly improve the learning and motivation of our students, also taking into account individualized learning [53,54]. Our results show a high acceptance by the students, according to the results of other authors [25,55].…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Verde and Valero on "Teaching and Learning Modalities in Higher Education During the Pandemic: Responses to Coronavirus Disease 2019 From Spain", stressed that the findings can be used to consider the advantages and disadvantages of various teaching and learning methods in higher education. The current circumstance necessitates that we continue to consider the best teaching style in order to ensure that kids' education is not jeopardized [13].…”
Section: Challenge On Modalitiesmentioning
confidence: 99%